Aromatic polysulfone composition, molded article, and method for producing molded article
By adding fatty acid compounds to the aromatic polysulfone composition, the problem of reducing the strength of the aromatic polysulfone composition in the prior art is solved, and an excellent balance between fluidity and strength is achieved.
Patent Information
- Application Number
- CN202380050078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-14
AI Technical Summary
When using aromatic polysulfone compositions as molding material, it is difficult for the prior art to effectively fill the composition in the fine structures in the mold, and compositions containing liquid crystal polyester will cause a decrease in strength when manufacturing the molded body.
The fluidity of the composition is increased and the strength of the molded body is reduced by adding at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives to the aromatic polysulfone composition.
The balance of fluidity and strength is achieved, ensuring good filling in the fine structural parts and high strength of the molded body.
Smart Images

Figure BDA0005211287960000251 
Figure BDA0005211287960000271 
Figure HDA0005211287970000011
Abstract
Description
Technical Field
[0001] The present invention relates to an aromatic polysulfone composition, a molded body and a method for producing the molded body.
[0002] This application claims priority based on Japanese Patent Application No. 2022-113183 filed in Japan on July 14, 2022, and the contents are incorporated herein by reference. Background Art
[0003] Aromatic polysulfones have excellent heat resistance, mechanical properties, electrical properties, hot water resistance, etc. Therefore, aromatic polysulfone compositions are used as molding materials for many applications such as electrical and electronic fields, mechanical fields, automobile fields, aircraft fields, and medical and food industry fields.
[0004] In addition, aromatic polysulfone is sometimes used in combination with other resins. For example, Patent Document 1 discloses a composition comprising an aromatic polysulfone resin having a specific melt viscosity, a liquid crystal polyester having a specific flow temperature, and a glass fiber having a specific average fiber diameter.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-20621 Summary of the invention
[0008] Problems to be solved by the invention
[0009] When an aromatic polysulfone composition is used as a molding material to produce a molded product, the composition can be easily filled even in fine structural parts in a mold by improving the fluidity of the aromatic polysulfone composition, which is suitable for producing a molded product having a fine structure.
[0010] The aromatic polysulfone composition containing a liquid crystal polyester can improve the fluidity of the composition by containing the liquid crystal polyester. However, in the resin composition disclosed in Patent Document 1, the strength of the produced molded article is reduced due to the inclusion of the liquid crystal polyester.
[0011] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an aromatic polysulfone composition having an excellent balance between fluidity and strength.
[0012] Means for solving problems
[0013] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that by containing at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives, the degree of reduction in the strength of the molded body can be suppressed and the fluidity of the composition can be improved, thereby completing the present invention.
[0014] That is, the present invention has the following aspects.
[0015] <1> An aromatic polysulfone composition comprising:
[0016] Aromatic polysulfone,
[0017] Liquid crystal polyester, and
[0018] At least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives.
[0019] <2> According to the above <1> The aromatic polysulfone composition, wherein the mass ratio of the aromatic polysulfone to the liquid crystal polyester is the aromatic polysulfone / the liquid crystal polyester=95 / 5 to 70 / 30.
[0020] <3> According to the above <1> or <2> In the aromatic polysulfone composition, the content of the fatty acid compound is 0.1 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the total mass of the aromatic polysulfone and the liquid crystal polyester.
[0021] <4> According to the above <1> ~ <3> The aromatic polysulfone composition described in any one of the preceding claims contains 30% by mass or more and 95% by mass or less of the aromatic polysulfone based on 100% by mass of the total mass of the aromatic polysulfone composition.
[0022] <5> According to the above <1> ~ <4> The aromatic polysulfone composition described in any one of the preceding claims contains the fatty acid derivative, wherein the fatty acid derivative includes a fatty acid amide.
[0023] <6> According to the above <1> ~ <5> The aromatic polysulfone composition according to any one of the preceding claims, wherein the aromatic polysulfone is an aromatic polyethersulfone having a repeating unit represented by the following formula (S1).
[0024] (S1)-Ph 1 -SO2-Ph 2 -O-
[0025] [Where Ph 1 and Ph 2 Each independently represents a phenylene group. The hydrogen atoms in the above phenylene groups may also be independently substituted by an alkyl group, an aryl group or a halogen atom.]
[0026] <7> According to the above <1> ~ <6> The aromatic polysulfone composition according to any one of the preceding claims, wherein the liquid crystal polyester is a liquid crystal polyester having a repeating unit (1) represented by the following formula (1), a repeating unit (2) represented by the following formula (2), and a repeating unit (3) represented by the following formula (3).
[0027] (1)-O-Ar 1 -CO-
[0028] (2)-CO-Ar 2 -CO-
[0029] (3)-X-Ar 3 -Y-
[0030] [Wherein, Ar 1 Ar represents phenylene, naphthylene or biphenylene. 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4). X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 ,Ar 2 or Ar 3 The hydrogen atoms in the above-mentioned groups may be independently substituted by halogen atoms, alkyl groups or aryl groups.]
[0031] (4)-Ar 4 -Z-Ar 5 -
[0032] [Wherein, Ar 4 and Ar 5 Each independently represents a phenylene group or a naphthylene group. Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.]
[0033] <8> According to the above <1> ~ <7> The aromatic polysulfone composition described in any one of the preceding claims, further comprising a fibrous filler.
[0034] <9> A molded body comprising the above <1> ~ <8> The aromatic polysulfone composition described above.
[0035] <10> A method for producing a molded body, comprising: <1> ~ <8> The aromatic polysulfone composition described above is injection molded.
[0036] Effects of the Invention
[0037] According to the present invention, an aromatic polysulfone composition having an excellent balance between fluidity and strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a graph showing the relationship between the spiral flow length and the weld bending strength of the compositions of Examples and Reference Examples.
[0039] Figure 2 This is a graph showing the relationship between the flow elongation values of the compositions of Examples and Reference Examples and the blending amounts of the liquid crystal polyester and the fatty acid amide-based additive.
[0040] Figure 3 It is a schematic diagram explaining the flow path shape of the mold used for evaluating fluidity in Examples. DETAILED DESCRIPTION
[0041] Hereinafter, embodiments of the aromatic polysulfone composition, the molded article, and the method for producing the molded article of the present invention will be described.
[0042] 《Aromatic polysulfone composition》
[0043] The aromatic polysulfone composition of the embodiment contains aromatic polysulfone, liquid crystal polyester, and at least one fatty acid compound (hereinafter, sometimes simply referred to as “fatty acid compound”) selected from the group consisting of fatty acids, fatty acid salts, and fatty acid derivatives.
[0044] The aromatic polysulfone composition of the embodiment can significantly improve the fluidity of the composition by including both the liquid crystal polyester and the fatty acid compound. In addition, by including the fatty acid compound, the fluidity of the aromatic polysulfone composition can be improved while suppressing the decrease in strength.
[0045] The strength of the aromatic polysulfone composition of the embodiment is evaluated by measuring the weld bending strength of a test piece (molded article) described later.
[0046] The fluidity of the aromatic polysulfone composition of the embodiment is evaluated by the flow length of a molded product obtained by injection molding the aromatic polysulfone composition under predetermined conditions using a mold having a specific spiral flow path as described in [Evaluation of Fluidity] below.
[0047] Hereinafter, each component of the aromatic polysulfone, liquid crystal polyester and fatty acid compound blended in the aromatic polysulfone composition of the embodiment and optional components that may be blended as desired in the aromatic polysulfone composition of the embodiment will be described.
[0048] The total content of the aromatic polysulfone, the liquid crystal polyester and at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives can be 50 parts by mass or more and 100 parts by mass or less, and can be 55 parts by mass or more and 100 parts by mass or less, based on 100 parts by mass of the total mass of the aromatic polysulfone composition.
[0049] <Aromatic polysulfone>
[0050] Aromatic polysulfone is typically a resin having a repeating unit composed of a divalent aromatic group (a residue obtained by removing two hydrogen atoms bonded to the aromatic ring of an aromatic compound) and a sulfonyl group (—SO 2 —).
[0051] The aromatic polysulfone used in the present embodiment is preferably a so-called aromatic polyethersulfone having a repeating unit including a divalent aromatic group, a sulfonyl group, and an ether bond.
[0052] From the perspective of heat resistance and chemical resistance, the aromatic polysulfone preferably has a repeating unit represented by the following formula (S1) (hereinafter, sometimes referred to as "repeating unit (S1)".). The aromatic polysulfone may further have other repeating units such as one or more repeating units represented by the following formula (S2) (hereinafter, sometimes referred to as "repeating unit (S2)"), or a repeating unit represented by the following formula (S3) (hereinafter, sometimes referred to as "repeating unit (S3)".).
[0053] (S1)-Ph 1 -SO2-Ph 2 -O-
[0054] [Where Ph 1 and Ph 2 Each independently represents a phenylene group. The hydrogen atoms in the above phenylene groups may also be independently substituted by an alkyl group, an aryl group or a halogen atom.]
[0055] (S2)-Ph 3 -R-Ph 4 -O-
[0056] [Where Ph 3 and Ph 4 Each independently represents a phenylene group. The hydrogen atoms in the above phenylene groups may also be independently substituted by an alkyl group, an aryl group or a halogen atom. R represents an alkylene group, an oxygen atom or a sulfur atom.]
[0057] (S3)-(Ph 5 ) n -O-
[0058] [Where Ph 5 The hydrogen atoms in the phenylene group may be substituted by alkyl groups, aryl groups or halogen atoms. n represents an integer of 1 to 3. When n is 2 or more, multiple Ph 5 They may be the same or different.]
[0059] Ph 1~Ph 5 The phenylene group represented by any of the above may be p-phenylene, m-phenylene, or o-phenylene, but is preferably p-phenylene.
[0060] The alkyl group which may replace the hydrogen atom in the phenylene group has preferably a carbon number of 1 to 10. Specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, n-octyl, and n-decyl.
[0061] The aryl group which may substitute for the hydrogen atom in the phenylene group preferably has a carbon number of 6 or more and 20 or less. Specific examples thereof include phenyl, o-tolyl, m-tolyl, p-tolyl, 1-naphthyl, and 2-naphthyl.
[0062] Examples of the halogen atom which may replace the hydrogen atom in the phenylene group include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0063] When the hydrogen atoms in the phenylene group are substituted with these groups, the number of these groups is preferably 2 or less, and more preferably 1, independently in each of the phenylene groups.
[0064] In the above, it is preferred that the hydrogen atoms in the phenylene group are not substituted.
[0065] The carbon number of the alkylene group represented by R is preferably 1 to 5. Specific examples thereof include a methylene group, an ethylene group, an isopropylene group, and a 1-butylene group.
[0066] The aromatic polysulfone preferably has 50% or more of the repeating unit (S1), more preferably 80% or more, and even more preferably substantially only the repeating unit (S1) relative to the total number of all repeating units (100%). The term "substantially" herein means that the repeating unit (S1) is contained in an amount of 98% or more and 100% or less relative to the number of all repeating units (100%), and means that a small amount of impurities contained in the raw material monomers may be contained. It should be noted that the aromatic polysulfone may also independently have two or more repeating units (S1) to (S3).
[0067] The reduced viscosity of aromatic polysulfones can also be more than 0.18dL / g, can also be more than 0.25dL / g and below 0.50dL / g, can also be more than 0.30dL / g and below 0.42dL / g. The higher the reduced viscosity of aromatic polysulfones, the easier it is to improve heat resistance and strength / rigidity. On the other hand, if the reduced viscosity of aromatic polysulfones is too high, then melt temperature and melt viscosity are easy to increase, and fluidity is easy to decrease. That is, if the reduced viscosity of aromatic polysulfones is within the above-mentioned range, then heat resistance and strength / rigidity are easy to increase, and melt temperature and melt viscosity are difficult to increase, and fluidity is difficult to decrease.
[0068] In this specification, the reduced viscosity (dL / g) of aromatic polysulfone refers to the value obtained by the following method. First, approximately 1 g of aromatic polysulfone is accurately weighed and dissolved in N,N-dimethylformamide, the volume of which is set to 1 dL. Next, the viscosity (η) of the solution and the viscosity (η0) of N,N-dimethylformamide as a solvent are measured at 25°C using an Ostwaldt viscometer. Next, the reduced viscosity of the aromatic polysulfone is obtained by dividing the specific viscosity ((η-η0) / η0) obtained from the measured value by the concentration of the above solution (approximately 1 g / dL).
[0069] The aromatic polysulfone composition of the embodiment may contain 30% by mass or more of the aromatic polysulfone, 30% by mass or more and 95% by mass or less, 40% by mass or more and 90% by mass or less, 45% by mass or more and 85% by mass or less, 50% by mass or more and 85% by mass or less, 50% by mass or more and 75% by mass or less, or 60% by mass or more and 75% by mass or less, relative to the total mass (100% by mass) of the aromatic polysulfone composition.
[0070] [Method for producing aromatic polysulfone]
[0071] Aromatic polysulfone can be produced by polycondensing a dihalogenated sulfone compound corresponding to the repeating unit constituting the aromatic polysulfone with a dihydroxy compound.
[0072] For example, the resin having the repeating unit (S1) can be produced by polycondensing a compound represented by the following formula (S4) as a dihalosulfone compound (hereinafter also referred to as "compound (S4)") and a compound represented by the following formula (S5) as a dihydroxy compound.
[0073] The resin having the repeating unit (S1) and the repeating unit (S2) can be produced by polycondensing the compound (S4) which is a dihalogenated sulfone compound and the compound represented by the following formula (S6) which is a dihydroxy compound.
[0074] The resin having the repeating unit (S1) and the repeating unit (S3) can be produced by polycondensing the compound (S4) which is a dihalogenated sulfone compound and the compound represented by the following formula (S7) which is a dihydroxy compound.
[0075] (S4)X 1 -Ph 1 -SO2-Ph 2 -X 2
[0076] [Wherein, X 1 and X 2 Each independently represents a halogen atom. 1 and Ph 2 Same meaning as above.]
[0077] (S5)HO-Ph 1 -SO2-Ph 2 -OH
[0078] [Where Ph 1 and Ph 2 Same meaning as above.]
[0079] (S6)HO-Ph 3 -R-Ph 4 -OH
[0080] [Where Ph 3 , Ph 4 and R has the same meaning as above.]
[0081] (S7)HO-(Ph 5 ) n -OH
[0082] [Where Ph 5 and n have the same meanings as above.]
[0083] The polycondensation of aromatic polysulfone is preferably carried out in a solvent using an alkali metal salt of carbonic acid. The alkali metal salt of carbonic acid may be a carbonate as a normal salt, a bicarbonate (bicarbonate) as an acidic salt, or a mixture of the two. As the carbonate, sodium carbonate and potassium carbonate are preferably used, and as the bicarbonate, sodium bicarbonate and potassium bicarbonate are preferably used.
[0084] As the solvent for polycondensation, an organic polar solvent is preferably used. Specific examples include dimethyl sulfoxide, 1-methyl-2-pyrrolidone, cyclopentane (also known as 1,1-dioxotetrahydrothiophene), 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, dimethyl sulfone, diethyl sulfone, diisopropyl sulfone, diphenyl sulfone, or a mixed solvent thereof.
[0085] <Liquid Crystal Polyester>
[0086] The liquid crystal polyester contained in the aromatic polysulfone composition of the present embodiment is not particularly limited as long as it is a polyester resin showing liquid crystal properties in a molten state. It should be noted that the liquid crystal polyester may also be a liquid crystal polyester amide, a liquid crystal polyester ether, a liquid crystal polyester carbonate, or a liquid crystal polyester imide.
[0087] The flow initiation temperature of the liquid crystal polyester is preferably 250° C. or higher, more preferably 270° C. or higher, and further preferably 280° C. or higher.
[0088] The flow start temperature of the liquid crystal polyester is preferably 400° C. or lower, more preferably 360° C. or lower, and further preferably 340° C. or lower.
[0089] For example, the flow start temperature of the liquid crystal polyester is preferably 250°C to 400°C, more preferably 270°C to 360°C, and further preferably 280°C to 340°C.
[0090] In this specification, the flow start temperature is also called fluid temperature or flow temperature, which is a temperature that serves as a standard for the molecular weight of liquid crystal polyester (see Naoyuki Koide, "Liquid Crystal Polymer - Synthesis, Molding, and Applications -", CMC Co., Ltd., June 5, 1987, p. 95).
[0091] The flow start temperature of the liquid crystal polyester is measured by, specifically, using a flow tester to make the liquid crystal polyester flow at 9.8 MPa (100 kg / cm 2 ) at a temperature at which the material is melted while being heated at a rate of 4°C / min under a load of 1°C and extruded from a nozzle having an inner diameter of 1 mm and a length of 10 mm to exhibit a viscosity of 4800 Pa·s (48000 poise).
[0092] The liquid crystal polyester is preferably a wholly aromatic liquid crystal polyester having only repeating units derived from aromatic compounds as raw material monomers.
[0093] Typical examples of liquid crystal polyesters include polymers obtained by polymerizing (polycondensing) aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, and at least one compound selected from the group consisting of aromatic diols, aromatic hydroxyamines, and aromatic diamines; polymers obtained by polymerizing a plurality of aromatic hydroxycarboxylic acids; polymers obtained by polymerizing aromatic dicarboxylic acids and at least one compound selected from the group consisting of aromatic diols, aromatic hydroxyamines, and aromatic diamines; and polymers obtained by polymerizing polyesters such as polyethylene terephthalate and aromatic hydroxycarboxylic acids.
[0094] Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may be replaced with a part or all of their derivatives which are independently polymerizable.
[0095] Examples of polymerizable derivatives of compounds having a carboxyl group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include compounds obtained by converting a carboxyl group into an alkoxycarbonyl group or an aryloxycarbonyl group (i.e., esters); compounds obtained by converting a carboxyl group into a haloformyl group (i.e., acyl halides); compounds obtained by converting a carboxyl group into an acyloxycarbonyl group (i.e., anhydrides), and the like.
[0096] Examples of polymerizable derivatives of compounds having a hydroxyl group such as aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxyamines include compounds in which the hydroxyl group is acylated to be converted into an acyloxy group (ie, acylates).
[0097] Examples of polymerizable derivatives of compounds having an amino group such as aromatic hydroxyamine and aromatic diamine include compounds obtained by acylation of the amino group to convert it into an acylamino group (ie, acylate).
[0098] The liquid crystal polyester preferably has a repeating unit represented by the following formula (1) (hereinafter also referred to as "repeating unit (1)"). The liquid crystal polyester more preferably has a repeating unit (1), a repeating unit represented by the following formula (2) (hereinafter also referred to as "repeating unit (2)"), and a repeating unit represented by the following formula (3) (hereinafter also referred to as "repeating unit (3)").
[0099] (1)-O-Ar 1 -CO-
[0100] (2)-CO-Ar 2 -CO-
[0101] (3)-X-Ar 3 -Y-
[0102] [Wherein, Ar 1 Ar represents phenylene, naphthylene or biphenylene. 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4). X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 ,Ar 2 or Ar 3 The hydrogen atoms in the above-mentioned groups may be independently substituted by halogen atoms, alkyl groups or aryl groups.]
[0103] (4)-Ar 4 -Z-Ar5 -
[0104] [Wherein, Ar 4 and Ar 5 Each independently represents a phenylene group or a naphthylene group. Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.]
[0105] As can be 1 ,Ar 2 or Ar 3 Examples of the halogen atom in which one or more hydrogen atoms in the above-mentioned groups are substituted include fluorine atom, chlorine atom, bromine atom and iodine atom.
[0106] As can be 1 ,Ar 2 or Ar 3 The alkyl group represented by the above groups substituted with one or more hydrogen atoms is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, n-octyl or n-decyl.
[0107] As can be 1 ,Ar 2 or Ar 3 The aryl group substituted with one or more hydrogen atoms in the above-mentioned groups represented by is preferably an aryl group having 6 to 20 carbon atoms, and examples thereof include phenyl, o-tolyl, m-tolyl, p-tolyl, 1-naphthyl, and 2-naphthyl.
[0108] In Ar 1 ,Ar 2 or Ar 3 When a hydrogen atom in the above-mentioned group represented by is substituted with the above-mentioned group, the number of substitutions is preferably 1 or 2, and more preferably 1.
[0109] The alkylene group in Z in formula (4) is preferably an alkylene group having 1 to 10 carbon atoms, and examples thereof include a methylene group, an ethylene group, an isopropylene group, an n-butylene group, and a 2-ethylhexylene group.
[0110] The liquid crystal polyester preferably has a repeating unit in which X and Y are each an oxygen atom as the repeating unit (3), that is, a repeating unit derived from an aromatic diol, because the melt viscosity tends to be low. It is more preferred to have only a repeating unit in which X and Y are each an oxygen atom as the repeating unit (3).
[0111] As the liquid crystal polyester having the above-mentioned repeating units (1) to (3), it is more preferable to have a repeating unit represented by the following formula (1-1), a repeating unit represented by the following formula (2-1), and a repeating unit represented by the following formula (3-1).
[0112] (1-1)-O-Ar 1-1 -CO-
[0113] (2-1)-CO-Ar 2-1 -CO-
[0114] (3-1)-O-Ar 3-1 -O-
[0115] As Ar 1-1 , represents 2,6-naphthylene, 1,4-phenylene or 4,4'-biphenylene.
[0116] As Ar 2-1 and Ar 3-1 , each independently represents 2,6-naphthylene, 2,7-naphthylene, 1,4-phenylene, 1,3-phenylene or 4,4′-biphenylene.
[0117] Ar 1-1 ,Ar 2-1 or Ar 3-1 The hydrogen atoms in the above-mentioned groups represented may each be independently substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0118] The repeating unit (1) is a repeating unit derived from an aromatic hydroxycarboxylic acid. As the repeating unit (1), Ar 1 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from p-hydroxybenzoic acid) or Ar 1 The repeating unit is a 2,6-naphthylene group (for example, a repeating unit derived from 6-hydroxy-2-naphthoic acid).
[0119] The term "source" as used herein means that the chemical structure of the functional group that contributes to the polymerization of the raw material monomer changes without causing other structural changes. The source here is a concept that also includes the case where the source is a polymerizable derivative of the raw material monomer.
[0120] The repeating unit (2) is a repeating unit derived from an aromatic dicarboxylic acid. As the repeating unit (2), Ar 2 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from terephthalic acid), Ar 2 is a repeating unit of 1,3-phenylene (for example, a repeating unit derived from isophthalic acid), Ar 2 is a repeating unit of 2,6-naphthylene (for example, a repeating unit derived from 2,6-naphthalenedicarboxylic acid) or Ar 2 is a repeating unit of diphenyl ether-4,4'-diyl (for example, a repeating unit derived from diphenyl ether-4,4'-dicarboxylic acid), more preferably Ar2 is a repeating unit of 1,4-phenylene, Ar 2 is a repeating unit of 1,3-phenylene or Ar 2 It is a repeating unit of 2,6-naphthylene.
[0121] The repeating unit (3) is a repeating unit derived from an aromatic diol, an aromatic hydroxylamine or an aromatic diamine. As the repeating unit (3), Ar 3 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from hydroquinone, p-aminophenol or p-phenylenediamine) or Ar 3 The repeating unit is a 4,4'-biphenylene group (for example, a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0122] The number of the repeating units (1) is preferably 30% to 80% of the total number (100%) of all repeating units constituting the liquid crystal polyester, more preferably 40% to 70%, further preferably 45% to 70%.
[0123] The number of the repeating units (2) is preferably 35% or less, more preferably 10% to 35%, and even more preferably 15% to 30%, based on the total number (100%) of all repeating units constituting the liquid crystal polyester.
[0124] The number of the repeating units (3) is preferably 35% or less, more preferably 10% to 35%, and even more preferably 15% to 30%, based on the total number (100%) of all repeating units constituting the liquid crystal polyester.
[0125] The ratio of the number of repeating units (2) to the number of repeating units (3), represented by [the number of repeating units (2)] / [the number of repeating units (3)], is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.
[0126] It should be noted that the liquid crystal polyester may also have two or more repeating units (1) to (3). In addition, the liquid crystal polyester may also have repeating units other than the repeating units (1) to (3), but the amount thereof is preferably 10% or less, more preferably 5% or less relative to the total number of all repeating units (100%).
[0127] In the present specification, the number of each repeating unit (polymerization degree of each repeating unit) can be determined by the analysis method described in Japanese Patent Application Laid-Open No. 2000-19168.
[0128] Specifically, the liquid crystal polyester is reacted with a lower alcohol (an alcohol having 1 to 3 carbon atoms) in a supercritical state to depolymerize the liquid crystal polyester to monomers derived from its repeating units. The monomers derived from each repeating unit obtained as the depolymerization product are quantified by liquid chromatography, and the number of each repeating unit can be calculated.
[0129] For example, in the case where a liquid crystal polyester is composed of repeating units (1) to (3), the number of repeating units (1) can be determined by calculating the molar concentrations of monomers from which repeating units (1) to (3) are derived, respectively, by liquid chromatography, and by calculating the ratio of the molar concentrations of monomers from which repeating units (1) to (3) are derived, when the total molar concentrations of monomers from which repeating units (1) to (3) are derived is set to 100%.
[0130] The liquid crystal polyesters may be used alone or in combination of two or more.
[0131] [Method for producing liquid crystal polyester]
[0132] Liquid crystal polyester can be produced by melt-polymerizing raw material monomers corresponding to the structural units constituting the liquid crystal polyester, and can be produced, for example, by the method described in Japanese Patent No. 6439027.
[0133] <Fatty acid compounds>
[0134] The fatty acid compound contained in the aromatic polysulfone composition of the present embodiment is at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts, and fatty acid derivatives.
[0135] The fatty acid is preferably a fatty acid having 12 or more carbon atoms, preferably a fatty acid having 12 or more and 28 or less carbon atoms, and more preferably a fatty acid having 12 or more and 20 or less carbon atoms. The fatty acid may be a saturated fatty acid or an unsaturated fatty acid.
[0136] Specific examples of the fatty acid having 12 or more carbon atoms include lauric acid, tridecyl acid, myristic acid, pentadecyl acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, nonadecanoic acid, arachidic acid, heneicosanoic acid, behenic acid, and montanic acid.
[0137] As the fatty acid salt, a fatty acid metal salt is preferred. Examples of the metal of the fatty acid metal salt include calcium, lithium, barium, aluminum, potassium, and sodium.
[0138] Examples of the fatty acid in the fatty acid salt include the fatty acids having 12 or more carbon atoms listed above, preferably fatty acid salts of fatty acids having 12 or more and 28 or less carbon atoms, and more preferably fatty acid salts of fatty acids having 12 or more and 20 or less carbon atoms.
[0139] Preferred specific examples of fatty acid salts include stearates such as calcium stearate, lithium stearate, barium stearate, aluminum stearate, potassium stearate, and sodium stearate.
[0140] As fatty acid derivatives, fatty acid esters and fatty acid amides can be cited. From the viewpoint of further improving the fluidity of the composition and suppressing the reduction in strength of the molded body, the fatty acid derivative preferably includes fatty acid amide, or may be substantially composed of only fatty acid amide. Here, "substantially" means that the total mass of the fatty acid derivative contains 98% or more and 100% or less of fatty acid amide.
[0141] Examples of the fatty acid in the fatty acid derivative include the fatty acids having 12 or more carbon atoms listed above, preferably fatty acid derivatives of fatty acids having 12 or more and 28 or less carbon atoms, and more preferably fatty acid derivatives of fatty acids having 12 or more and 20 or less carbon atoms.
[0142] Specific examples of the fatty acid amide having 12 or more carbon atoms include lauric acid amide, tridecyl acid amide, myristic acid amide, pentadecyl acid amide, palmitic acid amide, heptadecanyl acid amide, stearic acid amide, oleic acid amide, nonadecanyl acid amide, arachidic acid amide, heneicosanoic acid amide, behenic acid amide, and montanic acid amide.
[0143] In this specification, fatty acid amide is a concept including fatty acid bisamide. Fatty acid amide is preferably fatty acid bisamide.
[0144] Preferred specific examples of fatty acid bisamides include stearic acid derivatives such as ethylene bisstearic acid amide and ethylene bishydroxystearic acid amide.
[0145] Fatty acid amide and fatty acid bisamide are any fatty acid amide having a fatty acid amide structure (R 0 -CO-NH-. R 0 It represents a hydrocarbon chain derived from a fatty acid which may have a substituent. ) may have any substituent or structure.
[0146] <Optional Ingredients>
[0147] The aromatic polysulfone composition of the present embodiment may contain one or more fillers, a resin other than the aromatic polysulfone and the liquid crystal polyester, an additive, and other optional components as necessary.
[0148] The aromatic polysulfone composition of the present embodiment may contain the above-mentioned aromatic polysulfone, liquid crystal polyester, fatty acid compound and optional components used as required so that the total of their contents (mass %) in the aromatic polysulfone composition does not exceed 100 mass % with respect to the total mass (100 mass %) of the aromatic polysulfone composition of the embodiment.
[0149] The aromatic polysulfone composition of the present invention also includes the aromatic polysulfone, liquid crystal polyester, fatty acid compound, and optional components as required, which are described as the ingredients of the aromatic polysulfone composition and the reaction products of these components.
[0150] (filler)
[0151] The aromatic polysulfone composition of the present embodiment may further contain a filler.
[0152] The filler may be a fibrous filler, a plate-like filler, a granular filler, etc. In addition, the filler may be an inorganic filler or an organic filler.
[0153] The aromatic polysulfone composition of the present embodiment preferably further contains a fibrous filler.
[0154] The fibrous filler may be a fibrous inorganic filler or a fibrous organic filler.
[0155] Examples of the fibrous inorganic filler include glass fibers; carbon fibers; ceramic fibers such as silica fibers, alumina fibers, or silica alumina fibers; metal fibers such as iron, gold, copper, aluminum, brass, or stainless steel; silicon carbide fibers; or boron fibers.
[0156] In addition, examples of the fibrous inorganic filler include whiskers such as potassium titanate whiskers, barium titanate whiskers, wollastonite whiskers, aluminum borate whiskers, silicon nitride whiskers, and silicon carbide whiskers.
[0157] Examples of the fibrous organic filler include polyester fibers, para- or meta-aramid fibers, and PBO fibers.
[0158] As the fibrous filler in the present embodiment, among the above, glass fiber or carbon fiber is preferred, and glass fiber is more preferred.
[0159] Fiberglass
[0160] The type of glass fiber is not particularly limited, and known glass fibers can be used. Examples of the glass fiber include glass fibers produced by various methods such as chopped glass fibers and milled glass fibers.
[0161] Other examples include E glass (ie, alkali-free glass), C glass (ie, glass suitable for acid-resistant applications), AR glass (ie, glass suitable for alkali-resistant applications), S glass, and T glass.
[0162] The glass fiber may be a glass fiber that has not been surface-treated or a glass fiber that has been surface-treated.
[0163] The treatment of the glass fiber can be performed with a modifier, a silane coupling agent, a boron compound, etc. Examples of the modifier include aromatic urethane modifiers, aliphatic urethane modifiers, and acrylic modifiers.
[0164] As the glass fiber, among the above, E glass is preferred.
[0165] The preferred fiber diameter (single fiber diameter) of glass fiber can be determined by the raw material of the manufacturing method of the aromatic polysulfone composition described later, and the fiber diameter (single fiber diameter) of glass fiber is preferably more than 5 μm and less than 20 μm. In the case where the fiber diameter of glass fiber is more than 5 μm, compared with the case where the fiber diameter is less than 5 μm, the operation becomes easy and the production efficiency can be improved. The fiber diameter of glass fiber is more preferably more than 5.5 μm, more preferably more than 6 μm, especially preferably more than 8 μm, and particularly preferably more than 10 μm. In addition, in the case where the fiber diameter of glass fiber is less than 20 μm, compared with the case where the fiber diameter exceeds 20 μm, the fluidity of the aromatic polysulfone composition is improved, and then the effect of the glass fiber as the reinforcing material of the molded body is further improved. The fiber diameter of glass fiber is more preferably less than 17 μm, more preferably less than 15 μm.
[0166] As an example of the numerical range of the fiber diameter (single fiber diameter) of the above-mentioned glass fiber, it is preferably greater than 5 μm and less than 20 μm, more preferably greater than 5.5 μm and less than 17 μm, further preferably greater than 6 μm and less than 15 μm, especially preferably greater than 8 μm and less than 15 μm, and particularly preferably greater than 10 μm and less than 15 μm.
[0167] It should be noted that the diameter of the glass fibers does not substantially change even after melt kneading during melt molding.
[0168] In addition, "the fiber diameter of the glass fiber as a raw material" means the value measured by the "A method" among the methods described in "7.6 Single fiber diameter" of JIS R3420 unless otherwise specified.
[0169] The number average fiber length of the glass fiber as a raw material is preferably 20 μm or more, more preferably 1000 μm or more, and further preferably 2000 μm or more. The number average fiber length of the glass fiber is preferably 6000 μm or less, more preferably 5000 μm or less, and further preferably 4500 μm or less.
[0170] As an example of the numerical range of the number average fiber length of the glass fiber, it is preferably 20 μm or more and 6000 μm or less, more preferably 1000 μm or more and 5000 μm or less, and further preferably 2000 μm or more and 4500 μm or less.
[0171] In addition, in this specification, "the number average fiber length of the glass fiber as a raw material" means the value measured by the method described in JIS R3420 "7.8 Length of chopped strands" unless otherwise specified.
[0172] Carbon fiber
[0173] The type of carbon fiber is not particularly limited, and known carbon fibers can be used, and for example, PAN-based, pitch-based, rayon-based, phenol-based, or lignin-based carbon fibers are preferred.
[0174] In addition, for the purpose of imparting conductivity, carbon fibers coated with a metal such as nickel, copper, or ytterbium may be used.
[0175] The content of the fibrous filler in the above-mentioned aromatic polysulfone composition is preferably 1 mass part or more, more preferably 10 mass parts or more, and further preferably 15 mass parts or more relative to 100 mass parts of the total mass of the aromatic polysulfone and the liquid crystal polyester. In addition, the content of the fibrous filler is preferably 100 mass parts or less, more preferably 85 mass parts or less, and further preferably 50 mass parts or less relative to 100 mass parts of the total mass of the aromatic polysulfone and the liquid crystal polyester. The above-mentioned upper limit and lower limit can be combined arbitrarily.
[0176] As an example of the numerical range of the content of the fibrous filler in the aromatic polysulfone composition of the embodiment, it is preferably 1 part by mass or more and 100 parts by mass or less, more preferably 10 parts by mass or more and 85 parts by mass or less, and even more preferably 15 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of the total mass of the aromatic polysulfone and the liquid crystal polyester.
[0177] When the content of the fibrous filler is within the above-mentioned preferred range, the mechanical strength of the molded body can be further improved.
[0178] As resins other than the above-mentioned aromatic polysulfones and liquid crystal polyesters, thermoplastic resins such as polypropylene, polyamide, polyesters other than liquid crystal polyesters, polyphenylene sulfide, polyether sulfone, polyether ketone, polycarbonate, polyphenylene ether, or polyether imide can be listed; or thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, or cyanate resins. The aromatic polysulfone composition can also contain fluororesins such as polytetrafluoroethylene (PTFE). "Fluororesin" refers to a resin containing fluorine atoms in the molecule, and polymers having structural units containing fluorine atoms can be listed.
[0179] Examples of the additives include a release agent, a colorant (a pigment, a dye, carbon black, etc.), and the like.
[0180] The mass ratio of the aromatic polysulfone to the liquid crystal polyester in the aromatic polysulfone composition is preferably aromatic polysulfone / liquid crystal polyester = 95 / 5 to 65 / 35, more preferably 95 / 5 to 70 / 30, further preferably 95 / 5 to 75 / 25, particularly preferably 90 / 10 to 80 / 20.
[0181] By containing the aromatic polysulfone and the liquid crystal polyester in the above-mentioned mass ratio range, it is possible to easily provide an aromatic polysulfone composition having an excellent balance between fluidity and strength (for example, weld bending strength described later).
[0182] The content of at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives in the aromatic polysulfone composition is preferably 0.05 parts by mass or more and 5 parts by mass or less, more preferably 0.1 parts by mass or more and 1 part by mass or less, and even more preferably 0.1 parts by mass or more and 0.5 parts by mass or less, based on 100 parts by mass of the total mass of the aromatic polysulfone and the liquid crystal polyester.
[0183] By containing the fatty acid compound within the above-mentioned mass ratio range, an aromatic polysulfone composition having an excellent balance between fluidity and heat resistance can be easily provided.
[0184] Similarly, when the aromatic polysulfone composition further contains other resins other than the aromatic polysulfone and the liquid crystal polyester, the content of at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives in the aromatic polysulfone composition is preferably 0.05 parts by mass or more and 5 parts by mass or less, more preferably 0.1 parts by mass or more and 1 part by mass or less, and even more preferably 0.1 parts by mass or more and 0.5 parts by mass or less, based on 100 parts by mass of the total mass of the aromatic polysulfone, the liquid crystal polyester and other resins.
[0185] As another aspect of the aromatic polysulfone composition of the embodiment, for example, relative to the total mass (100 mass %) of the aromatic polysulfone composition of the embodiment,
[0186] Preferably, there can be illustrated a composition in which the content of the aromatic polysulfone is 40% by mass or more and 90% by mass or less, the content of the liquid crystal polyester is 3% by mass or more and 40% by mass or less, the content of the fatty acid compound is 0.01% by mass or more and 1% by mass or less, and the content of the fibrous filler is 1% by mass or more and 50% by mass or less.
[0187] More preferably, there can be exemplified a composition in which the content of the aromatic polysulfone is 45% by mass or more and 85% by mass or less, the content of the liquid crystal polyester is 5% by mass or more and 35% by mass or less, the content of the fatty acid compound is 0.05% by mass or more and 0.8% by mass or less, and the content of the fibrous filler is 5% by mass or more and 30% by mass or less.
[0188] More preferably, there can be exemplified a composition in which the content of the aromatic polysulfone is 50% by mass or more and 75% by mass or less, the content of the liquid crystal polyester is 5% by mass or more and 30% by mass or less, the content of the fatty acid compound is 0.05% by mass or more and 0.8% by mass or less, and the content of the fibrous filler is 15% by mass or more and 25% by mass or less.
[0189] More preferably, there can be illustrated a composition having an aromatic polysulfone content of 60% by mass or more and 75% by mass or less, a liquid crystal polyester content of 5% by mass or more and 20% by mass or less, a fatty acid compound content of 0.05% by mass or more and 0.8% by mass or less, and a fibrous filler content of 15% by mass or more and 25% by mass or less.
[0190] As described above, the aromatic polysulfone composition of the embodiment including both the liquid crystal polyester and the fatty acid compound has significantly improved fluidity.
[0191] The mechanism by which the fluidity of the composition is significantly improved by including both the liquid crystal polyester and the fatty acid compound in the aromatic polysulfone composition is not clear. However, it is believed that the aromatic polysulfone and the liquid crystal polyester are generally incompatible, and it is inferred that the fatty acid compound can reduce the friction generated at the interface between the aromatic polysulfone phase and the liquid crystal polyester phase when the composition flows, and it is believed that the fluidity is effectively improved in the composition containing the aromatic polysulfone and the liquid crystal polyester.
[0192] In addition, the inclusion of the fatty acid compound hardly reduces the strength of the composition, and the aromatic polysulfone composition of the embodiment containing the fatty acid compound is a very useful composition having an excellent balance between fluidity and strength.
[0193] The aromatic polysulfone composition of the embodiment has an excellent balance between fluidity in a flowing state and strength and heat resistance in a cured state. Therefore, the aromatic polysulfone composition of the embodiment can be suitably used as a molding material for melt molding, and can be suitably used as a molding material for injection molding in particular.
[0194] [Method for producing aromatic polysulfone composition]
[0195] The aromatic polysulfone composition of the embodiment can be obtained by mixing the above-mentioned aromatic polysulfone, liquid crystal polyester, at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives, and optional components used as needed, all together or in an appropriate order.
[0196] According to the method for producing an aromatic polysulfone composition according to the embodiment, the aromatic polysulfone composition according to the embodiment can be produced.
[0197] The aromatic polysulfone, liquid crystal polyester, fatty acid compound and optional components, and their blending ratios can be exemplified by the contents described in the above-mentioned "Aromatic polysulfone composition".
[0198] As a method for producing the aromatic polysulfone composition according to the embodiment, a method for producing the aromatic polysulfone including a step of mixing the aromatic polysulfone, a liquid crystal polyester, and a fatty acid compound is exemplified.
[0199] In the production method, the mass ratio of the aromatic polysulfone to the liquid crystal polyester is preferably 95 / 5 to 65 / 35, more preferably 95 / 5 to 70 / 30, and even more preferably 90 / 10 to 80 / 20.
[0200] In the above-mentioned production method, the amount of at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives is preferably 0.05 mass parts or more and 5 mass parts or less, more preferably 0.1 mass parts or more and 1 mass part or less, and further preferably 0.1 mass parts or more and 0.5 mass parts or less, relative to 100 mass parts of the total mass of the above-mentioned aromatic polysulfone and the above-mentioned liquid crystal polyester.
[0201] The mixing is preferably performed by melt kneading. The aromatic polysulfone composition of the present embodiment can be provided in the form of pellets by melt kneading the aromatic polysulfone, liquid crystal polyester, fatty acid compound, and optional components used as required using an extruder.
[0202] Furthermore, components other than the aromatic polysulfone and the liquid crystal polyester (for example, optional components such as fatty acid compounds and additives) can be added to pellets obtained by melt-kneading the aromatic polysulfone and the liquid crystal polyester using an extruder, and the pellets can be provided as an aromatic polysulfone composition in a state of being attached to the surface of the pellets.
[0203] The aromatic polysulfone composition obtained in this way, in particular, pellets of the aromatic polysulfone composition can be preferably used as a molding material for a molded body described later.
[0204] Forming
[0205] The molded article of the embodiment is a molded article including the aromatic polysulfone composition of one embodiment of the present invention.
[0206] Examples of the molded article of the present embodiment include a molded article containing an aromatic polysulfone, a liquid crystal polyester, and at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts, and fatty acid derivatives.
[0207] As the molded article of the present embodiment, a molded article formed from the aromatic polysulfone composition of the embodiment can be exemplified.
[0208] The molded article of the embodiment can be produced using the aromatic polysulfone composition of the embodiment having excellent fluidity. Therefore, a molded article having a fine structure and having an excellent balance between strength and heat resistance can be provided.
[0209] The strength of the aromatic polysulfone composition of the embodiment can be evaluated by measuring the weld bending strength and tensile strength of the test piece (molded article) described below.
[0210] [Weld bending strength]
[0211] An injection molding machine (e.g., manufactured by Sumitomo Heavy Industries, Ltd., trade name "SE100EV-A") is used, with the composition of the test object as the molding material, under the conditions of a barrel temperature of 380°C, a mold temperature of 150°C, and an injection speed of 50 mm / sec, using a mold in the shape of a type A multi-purpose test piece (thickness 3 mm) specified in ISO 3167:93 having gates at both ends, to injection mold a test piece (molded body) for a welding test having a weld line in the center.
[0212] The obtained test pieces (molded articles) were subjected to a bending test in accordance with ISO 178 at 23°C, at a test speed of 2 mm / min, a support distance of 64 mm, an indenter width of 1 mm, and a radius of 5 mm at the tip of the indenter. The bending strength value was the average value of the results of the three test pieces.
[0213] The weld bending strength of the test piece of the aromatic polysulfone composition obtained by this measuring method is preferably 30 MPa or more, more preferably 35 MPa or more, and even more preferably 40 MPa or more.
[0214] The upper limit of the weld bending strength of the test piece is not particularly limited, but as an example, it may be 200 MPa or less, 150 MPa or less, or 100 MPa or less.
[0215] As an example of the numerical range of the weld bending strength of the test piece, it may be 30 MPa or more and 200 MPa or less, 35 MPa or more and 150 MPa or less, or 40 MPa or more and 100 MPa or less.
[0216] [tensile strength]
[0217] An injection molding machine (e.g., NEX50IV-5EG manufactured by Nissei Plastic Industry Co., Ltd.) was used to produce an ASTM No. 4 dumbbell test piece using the composition of the test object as the molding material at a cylinder temperature of 380°C, a mold temperature of 150°C, and an injection speed of 50 mm / sec.
[0218] The tensile strength of the obtained test piece (molded article) was measured in accordance with ASTM D638 at a tensile speed of 10 mm / min in an atmosphere of 23° C. The value of the tensile strength was an average value of the results for five test pieces.
[0219] The tensile strength of the test piece of the aromatic polysulfone composition obtained by this measuring method is preferably 100 MPa or more, more preferably 110 MPa or more, and even more preferably 120 MPa or more.
[0220] The upper limit of the tensile strength of the test piece is not particularly limited, but as an example, it may be 200 MPa or less, 175 MPa or less, or 150 MPa or less.
[0221] As an example of the numerical range of the tensile strength of the test piece, it may be 100 MPa or more and 200 MPa or less, 110 MPa or more and 175 MPa or less, or 120 MPa or more and 150 MPa or less.
[0222] When the fatty acid amide or fatty acid bisamide is contained, the tensile strength is less likely to decrease compared to the case where a fatty acid, a fatty acid metal salt or a fatty acid ester is contained.
[0223] The heat resistance of the aromatic polysulfone composition of the embodiment can be evaluated by measuring the deflection temperature under load of the test piece (molded article) described below.
[0224] [Deflection temperature under load]
[0225] An injection molding machine (e.g., manufactured by Nissei Plastic Industry Co., Ltd., trade name "NEX50IV-5EG") is used, the composition of the test object is used as the molding material, and a rod-shaped test piece (molded body) with a width of 12.7 mm, a length of 127 mm, and a thickness of 6.4 mm is manufactured under the conditions of a barrel temperature of 380°C, a mold temperature of 150°C, and an injection speed of 50 mm / sec.
[0226] The obtained test piece (molded article) was measured for deflection temperature under load (DTUL) at a load of 1.82 MPa and a temperature increase rate of 2° C. / min in accordance with ASTM D648.
[0227] The deflection temperature under load of the test piece of the aromatic polysulfone composition obtained by this measuring method is preferably 180° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher.
[0228] The upper limit of the load deflection temperature of the test piece is not particularly limited, but as an example, it can be 250°C or less, 240°C or less, or 230°C or less. As an example of the numerical range of the load deflection temperature of the test piece, it can be 180°C or more and 250°C or less, 190°C or more and 240°C or less, or 200°C or more and 230°C or less.
[0229] The molded article of the present embodiment can be used for all uses to which a resin composition can generally be applied.
[0230] Examples of the molded body of the present embodiment include electrical / electronic components such as connectors, sockets, IC sockets, burn-in sockets, relay parts, bobbins, optical pickups, oscillators, printed circuit boards, circuit substrates, semiconductor packages, or computer-related components; semiconductor manufacturing process-related components such as IC trays or wafer carriers; household electrical appliance components such as VTRs, televisions, irons, air conditioners, stereo equipment, vacuum cleaners, refrigerators, rice cookers, or lighting fixtures; lighting fixture components such as lamp reflectors or lamp holders; audio product components such as compact disks, laser discs (registered trademark), or speakers; communication equipment components such as ferrules for optical cables, telephone components, fax components, or modems; copier or printer-related components such as separation claws or heater brackets; impellers, fans Mechanical parts such as gears, gears, bearings, motor parts, or housings; automotive parts such as automotive mechanism parts, engine parts, engine room parts, electrical parts, or interior parts; cooking utensils such as microwave cooking pots or heat-resistant tableware; thermal or sound insulation materials such as floor materials or wall materials, supporting materials such as beams or columns, or building materials such as roofing materials, or civil construction materials; parts for aircraft, spacecraft, or aerospace equipment; components of radiation facilities such as atomic reactors; marine facility components, washing fixtures, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts or medical materials, sensor parts, sanitary spare parts, sports goods, leisure goods or cable ties, etc.
[0231] 《Method for producing a molded article》
[0232] As a method for producing a molded body, a method comprising molding the aromatic polysulfone composition of the embodiment into a desired shape can be cited. As the production method, a molding method corresponding to the shape of the desired molded body and the like can be selected. As a molding method, a melt molding method is preferred.
[0233] The method for producing the aromatic polysulfone composition of the embodiment may include melt-molding the aromatic polysulfone composition of one embodiment of the present invention.
[0234] Examples of the melt molding method include injection molding, blow molding, vacuum molding, and press molding. Among them, injection molding is preferred.
[0235] The method for producing the aromatic polysulfone composition of the embodiment may include injection molding the aromatic polysulfone composition of one embodiment of the present invention.
[0236] For example, when the pellets of the aromatic polysulfone composition are used as the molding material and molding is performed by injection molding, the pellets of the aromatic polysulfone composition can be melted using a known injection molding machine and the melted pellets of the aromatic polysulfone composition can be injected into a mold for molding.
[0237] Examples of known injection molding machines include NEX50IV-5EG manufactured by Nissei Plastic Industries, Ltd. and SE100EV-A manufactured by Sumitomo Heavy Industries, Ltd.
[0238] The temperature conditions for injection molding are appropriately determined according to the types of aromatic polysulfone and liquid crystal polyester resin. Other injection conditions may be appropriately adjusted such as mold temperature, screw speed, back pressure, injection speed, holding pressure or holding time.
[0239] According to the method for producing a molded article of the embodiment, since the molded article is produced using the aromatic polysulfone composition of the embodiment, a molded article having a fine structure can be produced, and the produced molded article has an excellent balance between strength and heat resistance.
[0240] Example
[0241] Next, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to the following Examples.
[0242] <Manufacturing of Liquid Crystal Polyester>
[0243] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer, and a reflux cooler, 6-hydroxy-2-naphthoic acid (1034.99 g, 5.5 mol), 2,6-naphthalenedicarboxylic acid (378.33 g, 1.75 mol), terephthalic acid (83.07 g, 0.5 mol), hydroquinone (272.52 g, 2.475 mol, 0.225 mol excess relative to the total molar amount of 2,6-naphthalenedicarboxylic acid and terephthalic acid), acetic anhydride (1226.87 g, 12 mol) and 1-methylimidazole (0.17 g) as a catalyst were added. After replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes while stirring under a nitrogen flow, and refluxed at 145° C. for 1 hour.
[0244] Next, while distilling off by-produced acetic acid and unreacted acetic anhydride, the temperature was raised from 145°C to 310°C over 3 hours and 30 minutes. After maintaining at 310°C for 3 hours, the solid prepolymer (reaction mixture) was taken out and cooled to room temperature.
[0245] Next, the cooled prepolymer was crushed using a pulverizer until the particle size was about 0.1 mm to 1 mm. The obtained crushed material was heated from room temperature to 250°C in 1 hour under a nitrogen atmosphere, and from 250°C to 302°C in 8 hours and 40 minutes, and maintained at 302°C for 5 hours, thereby performing solid phase polymerization. The solid phase polymer was cooled to obtain a powdered liquid crystal polyester. The flow start temperature of the obtained liquid crystal polyester was 320°C.
[0246] <Manufacturing of resin composition>
[0247] (Material)
[0248] Aromatic polyethersulfone:
[0249] Sumitomo Chemical Co., Ltd. "SUMIKAEXCEL (registered trademark) PES3600P", polyethersulfone, reduced viscosity 0.36 dL / g
[0250] Liquid crystal polyester:
[0251] The liquid crystal polyester produced in the above method
[0252] Fatty acid amide additives:
[0253] "Light Amide WH-510K" manufactured by Kyoeisha Chemical Co., Ltd.
[0254] Glass fiber:
[0255] Made by Nitto Bosho, "CS3J260S", fiber diameter 11μm, number average fiber length 3.0mm
[0256] [Reference Examples 1 to 7, Examples 1 to 9]
[0257] Aromatic polyethersulfone, liquid crystal polyester, fatty acid amide additive, and glass fiber were blended in the amounts (parts by mass) shown in Table 1 and fed into a twin-screw extruder (PCM-30, manufactured by Ikegai Co., Ltd.), and granulated at a barrel temperature of 340° C. to obtain a resin composition (pellets) of each example.
[0258] <Manufacturing of Molded Article>
[0259] [Evaluation of liquidity]
[0260] An injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., trade name "SE100EV-A") was used, and a mold having a spiral flow path with a width of 8 mm and a thickness of 1 mm was used as the mold inner shape to evaluate the flow length (flow path shape refers to Figure 3 ). Figure 3In the figure, G represents a gate connected to the flow path, and the composition flows into the gate by a direct gate method. The resin composition of each example is used as a molding material for injection molding. Under the conditions of a barrel temperature of 380°C, a mold temperature of 150°C, an injection speed of 50 mm / sec, and a metering position of 25 mm in the above-mentioned molding machine, pressure control is replaced at the stage where the injection pressure reaches 150 MPa, and 150 MPa is continuously applied for an injection time of 2 seconds to obtain a molded body. The distances of 10 molded bodies from the end of the flow are measured, and the average value is taken as the flow length.
[0261] (Manufacture of test pieces for heat resistance and tensile strength tests)
[0262] An injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name "NEX50IV-5EG") was used to manufacture ASTM No. 4 dumbbell test pieces and rod-shaped test pieces with a width of 12.7 mm, a length of 127 mm, and a thickness of 6.4 mm under the conditions of a barrel temperature of 380°C, a mold temperature of 150°C, and an injection speed of 50 mm / sec.
[0263] (Manufacture of Test Specimens for Weld Bending Strength Test)
[0264] An injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., trade name "SE100EV-A") was used, with the resin composition of each example as the molding material, under the conditions of a cylinder temperature of 380°C, a mold temperature of 150°C, and an injection speed of 50 mm / sec, and a mold in the shape of a type A multi-purpose test piece (thickness 3 mm) specified in ISO 3167:93 having gates at both ends, to produce a test piece for a welding test having a weld line in the center.
[0265] [Measurement of weld bending strength]
[0266] The test pieces for the welding test prepared using the resin composition of each example were subjected to a bending test at 23°C at a test speed of 2 mm / min, a support distance of 64 mm, a width of the indenter of 1 mm, and a radius of 5 mm at the tip of the indenter in accordance with ISO 178. The bending strength value was the average value of the results of the three test pieces.
[0267] [Determination of tensile strength]
[0268] The tensile strength of ASTM No. 4 dumbbell test pieces prepared using the resin composition of each example was measured at a tensile speed of 10 mm / min in an atmosphere of 23° C. in accordance with ASTM D638. The value of the tensile strength was an average value of the results for 5 test pieces.
[0269] [Determination of deflection temperature under load (°C)]
[0270] The rod-shaped test piece produced using the resin composition of each example was measured for the deflection temperature under load (DTUL) at a load of 1.82 MPa and a temperature increase rate of 2° C. / min in accordance with ASTM D648.
[0271] The above measurement results are shown in Table 1 and Figures 1-2 middle. Figure 1 This is a graph showing the relationship between the spiral flow length and the bending strength.
[0272]
[0273] The results of Reference Examples 1 to 4 show that the fluidity of the resin composition can be improved as the amount of the liquid crystal polyester added increases, but it is confirmed that the weld bending strength decreases as the amount of the liquid crystal polyester added increases.
[0274] Therefore, it was found that, regarding the compositions of Reference Examples 1 to 4, unless a certain degree of decrease in weld bending strength is allowed, improvement in the fluidity of the resin composition due to the addition of the liquid crystal polyester cannot be expected.
[0275] Therefore, as shown in Examples 1 to 9, when a fatty acid amide-based additive was further added, the flowability of the resin composition could be improved without causing a significant decrease in the weld bending strength.
[0276] For example, the fluidity (spiral flow length) at a weld bending strength of 43 MPa in Reference Example 4 was 310 mm. In contrast, the spiral flow length of Example 3, which contained 0.1 parts by mass of a fatty acid amide additive and exhibited a similar weld bending strength of 43 MPa, was improved to 343 mm (see Tables 1, Figure 1 ).
[0277] This can also be said that when resin compositions having desired fluidity are compared with each other, the weld bending strength is improved by adding the fatty acid amide-based additive.
[0278] For example, the weld bending strength value of Reference Example 4 at the time of fluidity (spiral flow length value 310 mm) was 43 MPa. In contrast, the weld bending strength value of Example 2, which exhibited the same fluidity (spiral flow length 296 mm) with 0.1 parts by mass of the fatty acid amide-based additive, was improved to 58 MPa (see Tables 1, Figure 1 ).
[0279] Figure 2 This is a graph showing the relationship between the flow elongation values shown in Table 1 and the blending amounts of the liquid crystal polyester and the fatty acid amide-based additive.
[0280] Even when only focusing on the effect of improving fluidity, it was found that the resin compositions of Examples 1 to 9 containing both liquid crystal polyester and fatty acid amide additives had significantly improved fluidity compared to Reference Examples 5 to 7 containing no fatty acid amide additives.
[0281] When focusing on the heat resistance evaluated by the deflection temperature under load (° C.), all of Examples 1 to 9 exhibited good heat resistance (Table 1).
[0282] <Study on the types of additives>
[0283] [Reference Examples 8 to 15]
[0284] As additives, the following types of additives were studied.
[0285] ·Barium stearate (manufactured by Sakai Chemical Industry Co., Ltd.)
[0286] · Stearic acid (manufactured by Shin Nippon Rika Co., Ltd., Stearic acid 5000)
[0287] ·Polyol fatty acid ester (produced by Emery Oleochemicals Japan Co., Ltd., LOXIOL G15)
[0288] ・Fatty acid amide additive (Light Amide WH-510K, manufactured by Kyoeisha Chemical Co., Ltd.)
[0289] ・Fatty acid amide additive (Light Amide WH-255, manufactured by Kyoeisha Chemical Co., Ltd.)
[0290] ·Stearic acid amide (MCC TRADING Co., Ltd., AMIDE AP-1)
[0291] ·Ethylene bisstearamide (manufactured by MCC TRADING Co., Ltd., Slipax E)
[0292] In the same manner as in Reference Examples 1 and 5, aromatic polyethersulfone PES 3600P (100 parts by mass), the additives shown in Table 2 (0 parts by mass or 0.3 parts by mass) and glass fiber (20 parts by mass) were mixed, placed in a twin-screw extruder (manufactured by Ikegai Co., Ltd., PCM-30), and granulated at a barrel temperature of 340° C. to obtain a resin composition (pellet) of each example.
[0293] Table 2 shows the above measurement results.
[0294]
[0295] From the results shown in Table 2, when any of the fatty acids, fatty acid salts and fatty acid derivatives were added as additives (Reference Examples 9 to 15), the fluidity was improved compared to the case where no additive was added (Reference Example 8).
[0296] Among these fatty acids, fatty acid salts and fatty acid derivatives, when a fatty acid amide-based additive corresponding to fatty acid amide or fatty acid bisamide is added (Reference Examples 12 to 15), the effect of improving fluidity is higher and a better tensile strength value is shown.
[0297] The above results show that the aromatic polysulfone composition of the embodiments of the present invention, which contains an aromatic polysulfone, a liquid crystal polyester and at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives, is an extremely useful composition that is preferred as a molding material for injection molding, as shown in the evaluation results of achieving an excellent balance between fluidity and various strengths and heat resistance.
[0298] Each configuration and combination of the embodiments are examples, and addition, omission, substitution and other changes of the configuration may be made without departing from the gist of the present invention. In addition, the present invention is not limited to the embodiments but only to the scope of the claims.
[0299] Industrial Applicability
[0300] According to the present invention, an aromatic polysulfone composition having an excellent balance between fluidity and strength can be provided.
Claims
1. An aromatic polysulfone composition comprising: Aromatic polysulfone, Liquid crystal polyester, and At least one fatty acid compound selected from the group consisting of fatty acids, fatty acid salts and fatty acid derivatives.
2. The aromatic polysulfone composition according to claim 1, wherein The mass ratio of the aromatic polysulfone to the liquid crystal polyester is the aromatic polysulfone / the liquid crystal polyester=95 / 5 to 70 / 30.
3. The aromatic polysulfone composition according to claim 1 or 2, wherein The content of the fatty acid compound is 0.1 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the total mass of the aromatic polysulfone and the liquid crystal polyester.
4. The aromatic polysulfone composition according to claim 1 or 2, wherein The aromatic polysulfone is contained in an amount of 30% by mass or more and 95% by mass or less based on 100% by mass of the total mass of the aromatic polysulfone composition.
5. The aromatic polysulfone composition according to claim 1 or 2, wherein Contains the fatty acid derivative, which contains fatty acid amide.
6. The aromatic polysulfone composition according to claim 1 or 2, wherein The aromatic polysulfone is an aromatic polyethersulfone having a repeating unit represented by the following formula (S1): <h2 style=";text-align:left;direction:ltr">(S1)-Ph<h2 style=";text-align:left;direction:ltr"> 1 <h2 style=";text-align:left;direction:ltr"> -SO2-Ph<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> -O- Where Ph 1 and Ph 2 Each independently represents a phenylene group; the hydrogen atoms in the phenylene group may also be independently substituted by an alkyl group, an aryl group or a halogen atom.
7. The aromatic polysulfone composition according to claim 1 or 2, wherein The liquid crystal polyester is a liquid crystal polyester having a repeating unit (1) represented by the following formula (1), a repeating unit (2) represented by the following formula (2), and a repeating unit (3) represented by the following formula (3). (1)-O-Ar 1 -WHAT- (2)-CO-Ar 2 -WHAT- (3)-X-Ar 3 -Y- In the formula, Ar 1 represents phenylene, naphthylene or biphenylene; Ar 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4); X and Y each independently represent an oxygen atom or an imino group (-NH-); Ar 1 ,Ar 2 or Ar 3 The hydrogen atoms in the groups represented may also be independently substituted by halogen atoms, alkyl groups or aryl groups; (4)-Ar 4 -Z-Ar 5 - In the formula, Ar 4 and Ar 5 Each independently represents a phenylene group or a naphthylene group; and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.
8. The aromatic polysulfone composition according to claim 1 or 2, wherein It further contains a fibrous filler. 9 . A molded article comprising the aromatic polysulfone composition according to claim 1 . 10 . A method for producing a molded article, comprising injection molding the aromatic polysulfone composition according to claim 1 or 2.
Citation Information
Patent Citations
Formation of electrode
JP1989039027A
Analytical method for composition of total aromatic liquid crystal polyester resin
JP2000019168A
Aromatic polysulfone resin composition and its molded article
JP2002020621A
Delivery support apparatus, delivery support method, and program
JP2022113183A